Gender Differences in Sales Staff Performance in the Insurance Industry - Bhaskar Reddy, C M; Thomas, Renny (Ushus Journal of Business Management, 2016)
This research article analyses gender differences in sales performance by comparing difference in the sales performance of male and female salespersons in the insurance industry in the city of Bangalore. The study used Independent T test for testing the difference among sales performance of men and women. The statistical difference obtained as a result of this study was significant. Male sales staff did comparatively better than women in sales performance. The study found that there are many reasons for men performing better than women in sales performance. Men and women were given training and were full time employees in the sales industry in these insurance companies.